PENGARUH EKSTRAK TUMBUHAN AKAR TUBA (Derris elliptica L.) TERHADAP DAYA TETAS TELUR IKAN LELE(Clarias gariepinus L.) - Wati, Yeni Sri (Pendidikan Biologi, 2014)
The exertion of fresh water fish (Clarias gariepinus L.) must back up supply in quality and quantity. The hatching egg process, effects by water quality. Akar tuba plant is a traditional as a fish chater in river and the river have exertion of a fresh water fish. This research aimed to find out effect of akar tuba extract (Derris elliptica L.) cathfish to hatchibility. The research was conducted January-February in Zoology laboratory of Biology FMIPA UNP. The research used completelly randomized design with 4 treatment and 6 replication. The treatment is A/control (0,000%), B (0,002%), C (0,003%) and D (0,004%) akar tuba extract. The parameter observed hacht of egg to larva after 2 days in incubation. The data analisys by ANOVA and continued by LSD. The result show that akar tuba extract desreases of hatch of egg a fresh water fish in treatment C (79,17%) (p<0,05) and not significant to normal larva and abnormal larva.